Macrophage activation syndrome due to juvenile amyopathic dermatomyositis with atypical onset - Esma İnan Yüksel; Betül Demir; Metin kaya Gürgöze; Ilknur Calik (Galenos Publishing House, 2022)
Macrophage activation syndrome (MAS) is a life-threatening condition associated with rheumatic diseases. It is rarely reported in juvenile dermatomyositis. An 8-year-old girl was admitted with complaints of joint swelling and psoriasiform plaques on the elbows. She was diagnosed with psoriatic arthritis, and methotrexate therapy was started. Three months later, she was readmitted with fever, fatigue, and weight loss. Hepatosplenomegaly was found on physical examination. The muscle strengths were 5/5. Dermatological examination revealed facial edema, widespread maculoerythematous rash, and xerosis. Erythematous-violaceous papulosquamous plaques were seen on the dorsal surfaces of the elbows and metacarpophalangeal and proximal interphalangeal joints. Based on the clinical and laboratory findings, the patient was considered to have MAS secondary to juvenile amyopathic dermatomyositis (JADM). The cutaneous manifestations seen in MAS are not specific but depend on the underlying rheumatic disease. Given the atypical onset, this was considered a case of JADM misdiagnosed as psoriasis, which rapidly progressed to MAS.